A field surveying on the geodetic control of engineering linear structures using a terrestrial laser scanner - Naminat, Oleksandr; Palamar, Alena (Geodesy and Cartography, 2019)
The method of geodetic control of the road pavement using TLS is presented. The use of the terrestrial laser scanner can avoid some of the disadvantages of classical methods for determining the deformation of objects. One of the main of them is a small amount of information about the position of individual parts of the object, in this case, linear engineering structures. The proposed technique for terrestrial laser scanning of pavement in order to determine its actual spatial position and real geometric shape allows to perform the required set of works with the least labor and time costs, and also to obtain data for further monitoring. The technique involves the construction of a three-dimensional model of pavement for its evaluation over a certain time interval with a similar model. In order to determine the coordinates by the TLS, the special spheres of known diameter were used. During the measurements, tribrachs on tripods were used, in which the spheres alternately changed to reflectors to eliminate the centering error. The accuracy of determining the coordinates of the temporary survey network relative to the base station was no more than ±27 mm. The accuracy estimation of the temporary survey network coordinates made in the “LeicaGeoOffice” software is presented. The network of permanent stations in Ukraine was used to determine the coordinates, the errors were calculated as the RMS deviation.